THE TREND OF PEMALI PRACTICES IN PREVENTING MISFORTUNE IN MARRIAGE FROM MAQASHID SHARIAH PERSPECTIVE: A STUDY OF LUYO COMMUNITY BELIEFS - Rafid. A, Noercholis (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This research aims to examine the traditional beliefs surrounding pemali in marriage practices within the Luyo community. Specifically, it explores the community’s understanding of pemali, the reasons behind these beliefs, and how they function as preventive measures to avoid misfortune or failure in marriage. The study investigates the cultural significance of pemali and its enduring influence on contemporary marriage rituals. The study employs a qualitative approach, using ethnographic methods such as participant observation and in-depth interviews with key informants from the Luyo community. Data were collected through fieldwork and analyzed thematically to uncover the underlying motivations and meanings attached to pemali practices. The research also draws on a literature review of similar cultural practices in Indonesia to provide a comparative analysis. The findings reveal that the Luyo community views pemali as a set of prohibitions imposed on brides and grooms to prevent calamities such as accidents or other misfortunes. These beliefs are deeply rooted in empirical experiences, either from personal encounters or the collective memory of the community. The study also highlights that pemali is perceived as a spiritual safeguard, with marriage seen as a long and sacred journey that is vulnerable to the interference of evil forces. Therefore, pemali serves as a protective measure to ensure marital success. This research contributes to the understanding of the persistence of traditional beliefs in modern marriage practices, specifically in the context of pemali. While previous studies have explored cultural beliefs in other regions of Indonesia, this study offers a unique focus on the Luyo community's specific practices and the experiential basis for their adherence. It provides new insights into how traditional beliefs are maintained and transmitted through generations in a contemporary setting. The study has implications for understanding the intersection of cultural traditions and modern life, particularly in the context of marriage. It sheds light on how communities like Luyo continue to rely on traditional preventive measures in marriage, which could influence both social practices and future research on cultural preservation. Additionally, these findings may inform local policymakers and cultural practitioners about the importance of integrating respect for traditional beliefs with evolving social norms.